Enhanced eosinophil-mediated inflammation associated with antibody and complement-dependent pneumonic insults in critical COVID-19 - Dong-Min Kim (Cell Reports, 2021)
Summary: Despite the worldwide effect of the coronavirus disease 2019 (COVID-19) pandemic, the underlying mechanisms of fatal viral pneumonia remain elusive. Here, we show that critical COVID-19 is associated with enhanced eosinophil-mediated inflammation when compared to non-critical cases. In addition, we confirm increased T helper (Th)2-biased adaptive immune responses, accompanying overt complement activation, in the critical group. Moreover, enhanced antibody responses and complement activation are associated with disease pathogenesis as evidenced by formation of immune complexes and membrane attack complexes in airways and vasculature of lung biopsies from six fatal cases, as well as by enhanced hallmark gene set signatures of Fcγ receptor (FcγR) signaling and complement activation in myeloid cells of respiratory specimens from critical COVID-19 patients. These results suggest that SARS-CoV-2 infection may drive specific innate immune responses, including eosinophil-mediated inflammation, and subsequent pulmonary pathogenesis via enhanced Th2-biased immune responses, which might be crucial drivers of critical disease in COVID-19 patients.